Feasibility of a prehabilitation programme dedicated to older patients with cancer before complex medical–surgical procedures: the PROADAPT pilot study protocol. Issue 4 (2nd April 2021) - Roche, Mélanie; Ravot, Christine; Malapert, Amélie; Paget-Bailly, Sophie; Garandeau, Charlène; Pitiot, Virginie; Tomatis, Mélanie; Riche, Benjamin; Galamand, Béatrice; Granger, Marion; Barbavara, Claire; Bourgeois, Chrystelle; et al.
Abstract : Background: Ageing is associated with an increased prevalence of comorbidities and sarcopenia as well as a decline of functional reserve of multiple organ systems, which may lead, in the context of the disease-related and/or treatment-related stress, to functional deconditioning. The multicomponent 'Prehabilitation & Rehabilitation in Oncogeriatrics: Adaptation to Deconditioning risk and Accompaniment of Patients' Trajectories (PROADAPT)' intervention was developed multiprofessionally to implement prehabilitation in older patients with cancer. Methods: The PROADAPT pilot study is an interventional, non-comparative, prospective, multicentre study. It will include 122 patients oriented to complex medical–surgical curative procedures (major surgery or radiation therapy with or without chemotherapy). After informed consent, patients will undergo a comprehensive geriatric assessment and will be offered a prehabilitation kit that includes an advice booklet with personalised objectives and respiratory rehabilitation devices. Patients will then be called weekly and monitored for physical and respiratory rehabilitation, preoperative renutrition, motivational counselling and iatrogenic prevention. Six outpatient visits will be planned: at inclusion, a few days before the procedure and at 1, 3, 6 and 12 months after the end of the procedure. The main outcome of the study is the feasibility of the intervention, defined as the ability to perform at least one of the components of the programme. Clinical data collected will include patient-specific and cancer-specific characteristics. Ethics and dissemination: The study protocol was approved by the Ile de France 8 ethics committee on 5 June 2018. The results of the primary and secondary objectives will be published in peer-reviewed journals. Trial registration number: NCT03659123 . Pre-results of the trial.